1989
DOI: 10.4141/cjps89-160
|View full text |Cite
|
Sign up to set email alerts
|

Fructans in Onion Bulbs in Relation to Storage Life

Abstract: SuzuKr, M. AND CurcLFFe, J. A. 1989. Fructans in onion bulbs in relation to storage life. Can. J. Plant Sci. 69: 132'7-1333. A 3-yr study with eight different onion cultivars , Allium cepa, was conducted to determine the association of water-soluble carbohydrates (WSC) with the storability of the bulbs. Onion bulbs were harvested in the fall of 1983, 1984 and 1985, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
2
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 7 publications
8
51
2
1
Order By: Relevance
“…The observation that 'Pole Star'-a variety that accumulates less FOSs-exhibited almost identical (or even stronger) enzyme activities in the biosynthetic pathway suggested that FOSs were at least produced in cultivar types such as 'Kita-momiji 2000' and 'Pole Star'. Suzuki and Cutcliffe (1989) reported that FOS contents were highest at harvest, and then decreased during storage while mono and disaccharides increased. Benkeblia et al (2005) ported that the degradative activities were changed during storage, leading to a change in sugar and FOS composition.…”
Section: Enzyme Activities In the Biosynthesis And Biodegradation Patmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that 'Pole Star'-a variety that accumulates less FOSs-exhibited almost identical (or even stronger) enzyme activities in the biosynthetic pathway suggested that FOSs were at least produced in cultivar types such as 'Kita-momiji 2000' and 'Pole Star'. Suzuki and Cutcliffe (1989) reported that FOS contents were highest at harvest, and then decreased during storage while mono and disaccharides increased. Benkeblia et al (2005) ported that the degradative activities were changed during storage, leading to a change in sugar and FOS composition.…”
Section: Enzyme Activities In the Biosynthesis And Biodegradation Patmentioning
confidence: 99%
“…As stated above, FOSs are important components of onions not only as a storage substance, but also contributing to culinary quality, tolerance against some environmental stresses, and even human health (Bouhnik et al, 1999;Delzenne et al, 1995;Pilon-Smits et al, 1995;Pollock et al, 1988;Suzuki and Cutcliffe, 1989). Thus, their content and composition are significant traits to be considered during the assessment of onion bulb quality.…”
Section: Varietal Differences In Sugar and Total Fos Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous investigations have been conducted on fructans in onion, including their distribution (Darbyshire & Henry, 1978) and changes during storage (Darbyshire, 1978;Rutherford & Whittle, 1982;Suzuki & Cutcliffe, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A concentração de inulina em cada planta depende muito da variedade, do tempo decorrido desde a colheita até a utilização desta e das condições de estocagem. Na cebola, dependendo destes fatores, a concentração de inulina pode chegar a até 50% da matéria seca (RUTHERFORD;WHITTLE, 1982;SUZUKI;CUTCLIFE, 1989).…”
Section: Ocorrência Naturalunclassified